Bio 3D Conduits Derived from Bone Marrow Stromal Cells Promote Peripheral Nerve Regeneration. (20th August 2020) - Yurie, Hirofumi; Ikeguchi, Ryosuke; Aoyama, Tomoki; Tanaka, Mai; Oda, Hiroki; Takeuchi, Hisataka; Mitsuzawa, Sadaki; Ando, Maki; Yoshimoto, Koichi; Noguchi, Takashi; Akieda, Shizuka; Nakayama, Koichi; et al.
We previously reported that a nerve conduit created from fibroblasts promotes nerve regeneration in a rat sciatic nerve model. This study aims to determine whether a nerve conduit created from bone marrow stromal cells (BMSCs) can promote nerve regeneration. Primary BMSCs were isolated from femur bone marrow of two Lewis rats, and cells at passages 4–7 were used. We created seven Bio 3D nerve conduits from BMSCs using a Bio-3D Printer. The conduits were transplanted to other Lewis rats to bridge 5-mm right sciatic nerve gaps (Bio 3D group, n = 7). We created two control groups: a silicone group (S group, n = 5) in which the same nerve gap was bridged with a silicone tube, and a silicone cell group (SC group, n = 5) in which the gap was bridged with a BMSC injection. Twelve weeks after transplantation, nerve regeneration was evaluated functionally and morphologically. In addition, PKH26-labeled BMSCs were used to fabricate a Bio 3D conduit that was transplanted for cell trafficking analysis. Electrophysiological study, kinematic analysis, wet muscle weight, and morphological parameters showed significantly better nerve regeneration in the Bio 3D group than in the S group or SC group. In immunohistochemical studies, sections from the Bio 3D group contained abundant S-100-positive cells. In cell trafficking analysis, PKH26-positive cells stained positive for the Schwann cell markers S-100, p75NTR, and GFAP. Bio 3D nerve conduits created from BMSCs can promote peripheral nerve regeneration in a rat sciatic nerve model through BMSC differentiation into Schwann-like cells.